The Russia balance sheet - Åslund, Anders 1952-; Kuchins, Andrew 1959- (Peterson Inst. for Internat. Economics, 2009)
Product Description: Russia projects a sense of renewed power and prominenence on the world stage; by 2020 it's expected to emerge as the fifth-largest economy in the world. Going forward, how the United States and Russia deal with each and with issues of mutual interest will have a significant impact around the globe. The Russia Balance Sheet sets forth a primer on Russia's current governmental and political infrastructure as well as its opportunity for growth. This important new book provides comprehensive, balanced, and accurate information on all key aspects of Russia and discusses what its status means for the US and other nations. To that end, the authors develop a cohesive, overarching framework that analyzes the nexus point of such areas as economic reforms and integration, domestic politics and society, foreign business partnerships, and energy demands. Based upon this foundation, the book capably suggests constructive policies for Russia and the next US administration that will take office in 2009.
Includes bibliographical references and index
Keywords: Außenwirtschaftspolitik; Geopolitik; Internationale Wirtschaftsbeziehungen; Politischer Wandel; Russland; Strukturwandel; Wirtschaftslage; Wirtschaftspolitik; Wirtschaftswachstum; Politik; Wirtschaft; Post-communism -- Russia (Federation); Russia (Federation) -- Economic conditions -- 1991-; Russia (Federation) -- Economic policy -- 1991-; Russia (Federation) -- Politics and government -- 1991-